Problem-solving in conservation biology and wildlife management : - Gibbs, James P. (Blackwell Science, 1998)
This book, intended as a supplement to a conservation biology or wildlife management textbook, provides a series of exercises for the field, lab or classroom. Topics range from population viability analysis to conservation planning, rare species occurrence, and gap analysis. The authors plan to develop a web site in conjunction with the book so that free-ware programmes and other information can be downloaded for use in some of the exercises.